2016
DOI: 10.4103/0973-6042.174513
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of the Nice knot

Abstract: Background:The Nice knot is a bulky double-stranded knot. Biomechanical data supporting its use as well as the number of half hitches required to ensure knot security is lacking.Materials and Methods:Nice knots with, one, two, or three half-hitches were compared with the surgeon's and Tennessee slider knots with three half hitches. Each knot was tied 10 times around a fixed diameter using four different sutures: FiberWire (Arthrex, Naples, FL), Ultrabraid (Smith and Nephew, Andover, MA), Hi-Fi (ConMed Linvatec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Another work compared an in-situ suture anchor repair and a transtibial technique with sutures tied over a titanium plate in a porcine model 10 In the transtibial pullout repair, the mean permanent displacement registered after 1000 cycles of a [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] N load was 2.2 mm with the transtibial technique. Again, notorious methodological dissimilarities difficult contrast of the result with our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another work compared an in-situ suture anchor repair and a transtibial technique with sutures tied over a titanium plate in a porcine model 10 In the transtibial pullout repair, the mean permanent displacement registered after 1000 cycles of a [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] N load was 2.2 mm with the transtibial technique. Again, notorious methodological dissimilarities difficult contrast of the result with our study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent work monitored the meniscus-suture interface and found no macroscopic damage at the meniscus-suture boundary up to a load close to ultimate failure 13 . This implies that sources other than suture cutout should contribute to generating permanent displacements, such as knot squeezing or slipping, since a certain degree of knot slippage under load has been reported 14,15 . In transtibial repair techniques, sutures are frequently fixed by tying them over a cortical button or a post at the distal end of the bone tunnel exit.…”
Section: Initial Biomechanical Properties Of Transtibial Meniscal Roomentioning
confidence: 99%
“…The biomechanical [ 21 ] comparison showed that high-performance sutures provided an alternative to steel wire for cerclage fixation, which had certain clinical application value. A recent biomechanical study [ 5 ] demonstrated that the Nice knot, especially using fiber wire, was biomechanically superior to the surgeon’s and Tennessee slider knots. P Collin [ 4 ] et al made a mechanical analysis of Nice knot, which provided an option for sliding and locking knots, which reduced the risk of elongation during dynamic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Prolene 4-0 (Ethicon, US), a single stranded synthetic nonabsorbable polypropylene monofilament suture was used to stitch the skin. The surgeon's knot was chosen as the knot technique of choice in our study because it is a simple and commonly adopted knot technique that has been shown to be superior to square and sliding knots in terms of knot security [4,[14][15][16]. For each specimen, a surgeon's knot with 3 throws (2-1-1) was made.…”
Section: Specimen Preparationmentioning
confidence: 99%